2016
DOI: 10.3389/fnsys.2016.00049
|View full text |Cite
|
Sign up to set email alerts
|

Universal Darwinism As a Process of Bayesian Inference

Abstract: Many of the mathematical frameworks describing natural selection are equivalent to Bayes' Theorem, also known as Bayesian updating. By definition, a process of Bayesian Inference is one which involves a Bayesian update, so we may conclude that these frameworks describe natural selection as a process of Bayesian inference. Thus, natural selection serves as a counter example to a widely-held interpretation that restricts Bayesian Inference to human mental processes (including the endeavors of statisticians). As … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 30 publications
3
108
0
2
Order By: Relevance
“…Our equations also decompose growth in a similar manner, but use diversity metrics like entropies and mutual information instead. This expands recent work that has shown that natural selection expressed through replicator dynamics can be reformulated in terms of relative Kullback-Leibler entropy D KL [24][25][26][27]. Especially Frank [28,29] has worked out a clear link between relative entropy and Fisher's fundamental theorem of natural selection [30].…”
Section: Evolutionary Economics: Decomposing Growth Descriptivelysupporting
confidence: 65%
“…Our equations also decompose growth in a similar manner, but use diversity metrics like entropies and mutual information instead. This expands recent work that has shown that natural selection expressed through replicator dynamics can be reformulated in terms of relative Kullback-Leibler entropy D KL [24][25][26][27]. Especially Frank [28,29] has worked out a clear link between relative entropy and Fisher's fundamental theorem of natural selection [30].…”
Section: Evolutionary Economics: Decomposing Growth Descriptivelysupporting
confidence: 65%
“…In terms of fitness, what matters is the time integral of variational free-energy (free action), given the locations that are actually visited (and outcomes experienced). More formally, from the perspective of the free-energy principle fitness corresponds to model evidence (Campbell, 2016, Frank, 2012): lnPtrue(trueo˜true)Ftrue(s˜,π,θitrue)…”
Section: Simulation Of Niche Constructionmentioning
confidence: 99%
“…The likelihood function is analogous to the fitness function and the posterior distribution to the selected population. Relations like this suggest that Bayesian update could be one of the pillars of “universal Darwinism” 33 . We believe that convincing models for neuro-evolution could empower Bayesian approaches by providing a mechanism to generate candidate hypotheses.…”
Section: Introductionmentioning
confidence: 96%